2022
DOI: 10.1007/s00170-022-09441-4
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of laser process parameters on the hardness profile of AISI 4340 cylindrical samples: statistical and experimental analyses

Abstract: In the present paper, continuous Nd:YAG laser hardening of cylindrical AISI 4340 steel specimens was studied using experimental and statistical analyses. Three Laser parameters namely laser power, laser feed speed, and sample rotation speed were selected to evaluate their in uence on the depth of the hardened zone, and the maximum surface hardness. Mathematical models were developed as a function of these three parameters and the analysis of variance (ANOVA) was used to conduct the statistical study. Microhard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Moreover, the geometric dimensions of the modified layer were greater than those created with solid-state lasers. The impact of surface texture was investigated by subjecting low-carbon steel to neodymium-doped yttrium aluminum garnet (Nd: YAG) and CO 2 laser beam irradiation within the energy range of 200 to 600 mJ [14]. The findings revealed that the extent of the affected zone is primarily governed by laser power and scanning speed, resulting in the creation of a superficial layer characterized by a uniform material thickness of approximately 2 mm.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the geometric dimensions of the modified layer were greater than those created with solid-state lasers. The impact of surface texture was investigated by subjecting low-carbon steel to neodymium-doped yttrium aluminum garnet (Nd: YAG) and CO 2 laser beam irradiation within the energy range of 200 to 600 mJ [14]. The findings revealed that the extent of the affected zone is primarily governed by laser power and scanning speed, resulting in the creation of a superficial layer characterized by a uniform material thickness of approximately 2 mm.…”
Section: Introductionmentioning
confidence: 99%